Kajian kecenderungan tuberkulosis di Kabupaten Minahasa Tenggara periode 2015-2017 - Siwi, Imelda; Ratag, Gustaaf A. E.; Kuhon, Frelly V. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2018)
Background: Tuberculosis (TB) is an infection caused by Mycobacterium tuberculosis. TB is one of the main problems for global health and is the cause of morbidity for millions each year. Indonesia ranked third on the highest incident of TB after India and China based on WHO 2017 report.Aim: This study is aimed to identify TB trends in Southeast Minahasa district from 2015 – 2017.Methods: This study is a descriptive study using cross sectional design to identify TB trends in Southeast Minahasa district from 2015-2017. This study used quantitative and qualitative as research method.Result: On 2015 to 2017 there is an increased incidence of tuberculosis from 140 to 189 cases. The main cause of the increasing TB cases are poverty in various community group on developing countries, failure of TB programs, demographic changes due to increasing world population and changes on population age structures, etc. Several factors that are related to Lungs TB are source of transmission, contact history with TB patients, level of exposure, basil virulence, low immunity system related to genetic factors, nutritional state, physiological factors, age, diet, immunization, housing conditions, work and economic status.Conclusion: Incidence rate of TB from 2015 to 2017 increased from 140 cases to 189 cases and mostly occur in men. Patients knowledge about transmission and prevention of lung TB is still lacking. Knowledge, attitude and behaviour is affected by age, education, social and environment factors. Lung TB patients know that duration of the treatment is 6 months without breaks in taking the medicines.